ABSTRACTS OF RESEARCH AND PRACTICE CONFERENCE “2ND ALL-RUSSIAN PEDIATRIC FORUM FOR STUDENTS AND YOUNG SCIENTISTS WITH INTERNATIONAL PARTICIPATION”, MAY 13-14, 2020, MOSCOW - Article Editorial (Педиатрическая фармакология)
The forum organizing committee presents students and young scientists researches approved by scientific commission (which includes academic staff from departments of N.F. Filatov Clinical Institute of Children's Health in Sechenov First Moscow State Medical University).